PENGARUH PEMBELAJARAN PJBL BERBASIS STEM TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI LISTRIK DINAMIS - Adhitya Rahardhian (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2022)
This research aims to determine the effect of the STEM-based PjBL model on students' critical thinking abilities on dynamic electrical material. The research method used is a quasi-experimental one-group pretest-posttest design. The sampling technique of this research is non-probability sampling in the form of purposive sampling, which takes a sample of 31 students from 8th grade SMP Negeri 2 Balai. The research instrument is the critical thinking test and student responses questionnaire. The critical thinking form test is multiple-choice accompanied by reasons totaling 10 questions. The student response questionnaire consisted of 15 questions. The STEM project that the students worked on was a miniature energy-efficient house. The result of questionnaires conducted by students, known majority of students has good responses to the STEM-based PjBL learning. The result of the paired t-test analysis using IBM SPSS Statistics 25, shows that Sig. (2-tailed) is 0.000. It means a significant difference average between the pretest and posttest scores. The students' average posttest scores were higher than the average pretest scores.